Il sistema politico e costituzionale della Russia un anno dopo la Grande Riforma Putiniana: tra legislazione attuativa, chiusura identitaria e fragilità politica (Nuovi Autoritarismi e Democrazie: Diritto, Istituzioni, Società (NAD-DIS), 2021)
The contribution takes stock of the intense legislative activity occurred in the last year in Russia. This has taken place against the background of a “frozen” political regime which is deeply concerned about the activity of “non-systemic” opposition and “foreign agents”, and increasingly aggressive in international relations.
Keywords: Russia; foreign agents; elections; freedom of gathering; xenophobia